Pengaruh Permainan Puzzle Terhadap Peningkatan Kreativitas Anak Usia 5-6 Tahun TK ABA DULANG Enrekang : Penelitian - Nur Alfilail; Herlina; A. Sri Wahyuni Asti; Sultan Sahrir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is motivated by the importance of stimulating creativity in children aged 5-6 years as a foundation for cognitive and social emotional development. The purpose of the study was to describe the application of puzzle games to increase the creativity of children aged 5-6 years at ABA Dulang Kindergarten, Enrekang Regency, describe changes in children's creativity before and after treatment, and determine the effect of puzzle games on increasing children's creativity. The method used was Quasi Experimental with a Non-Equivalent Control Group design, involving 25 children divided into experimental and control groups. Data collection was carried out through observation, pre-test and post-test. Data were analyzed descriptively and inferentially using the Wilcoxon Signed Rank Test. The results showed that the application of puzzle games provided an interactive and fun learning experience, significantly increasing children's creativity. Children's creativity in the experimental group increased from low to very good after being given puzzle games, while the control group only showed minimal improvement. Statistical test analysis confirmed the positive and significant effect of puzzle games on increasing the creativity of children aged 5-6 years at ABA Dulang Kindergarten. In conclusion, puzzle games are effective as a learning medium to stimulate early childhood creativity. It is recommended that teachers and parents integrate puzzle games as a learning method to optimize children's creativity development.